Uso das mídias no meio educacional: um estudo a partir das realidades em um estabelecimento público de Educação Infantil em Arraias-TO - Serafim, Pedro Alexandre (Universidade Federal do Tocantins, 2019)
This research aimed to the use of media in education, having as a field of study an instrument of early childhood education. In this case, we looked at how the media are used in the educational environment from a qualitative research. With the use of participatory observation and the application of questionnaires, we sought to collect data and information about the use of the media, as well as the conceptions of teachers as the same and how the utilities are used by educators. In view of the above, an analysis that aims to use the media in an irregular manner, revealing the need for training and awareness focused on the practice of media support. This is a mechanism that allows the evaluation of other initiatives and actions that trigger the learning of teachers about the school exercise of the media in the dynamics performed in the school space.